Penerapan Bahasa Jurnalistik pada Berita Utama di Koran Harian Jurnal Bogor Edisi 07-13 Juni 2017 Dan Edisi 05-11 Juli 2017 - Ratipah, Dede; Sobari, Ahmad; Rofi'ah, Rofi'ah (Universitas Ibn Khaldun Bogor, 2021)
The Application of Journalistic Language to Main News in Journal Bogor Daily Newspaper Issue 07-13 June 2017 and Issue 05-11 July 2017. Users and connoisseurs of mass media-primarily aimed at the mass media print whether it's in the form of newspapers, magazines, tabloids, or mass media other prints maybe a lot of what's been ignored enough the language of journalism or the language of the variety of journalism in their daily life. The reason, which is their focal point is not on the language, but what is mandated through the language device. Journalistic language is used by journalists called the press language of journalistic language. The language of journalism has distinctive characteristics: brief, solid, clear, democratic, simple, populist and interesting. Language of journalism based on the standard language, does not consider lax rules of grammar, pay attention to the correct spelling, in the journalistic language vocabulary followed developments in society. So, in this research formulated 2 (two) formulation of problem that is: How is the application of journalistic language in the headlines? And what the language of journalism is appropriate in the headlines? The purpose of this study is to knowing the applicability and appropriateness of journalistic language on the headlines at daily newspaper journals Bogor edition 07-13 June 2017 and 05-11 July 2017. This research uses qualitative approach with interview method depth (in-depth interview) where the researchers conduct direct interviews with Primed daily newspaper journal Bogor on how to apply the language of journalism on headlines in the form of titles and leads and analysing the contents of the suitability of journalistic language on the headlines titles and leads to describe it. By using in-depth interview method can generate data accurate direct from Primed regarding the application of journalistic language with analysing the contents of headlines in the form of titles and leads can be seen is enough both with the completeness of the principles of journalistic language has been met but there are some titles that are still less clear and less populist because most people still lay with the language of journalism or language press used in print media. The leads are pretty obvious with what will be delivered. In conclusion the application and appropriateness of journalistic language on the headlines is good enough because it consistently continues to use the principles of language journalism but in the implementation, there is still a mistake on the title which is less clear.AbstrakPara pengguna dan penikmat media massa-utamanya ditujukan pada media massa cetak, entah itu yang berbentuk surat kabar, majalah, tabloid, atau media massa cetak lainnya-mungkin sekali banyak yang selama ini tidak cukup memedulikan bahasa jurnalistik atau bahasa ragam jurnalistik dalam keseharian mereka. Alasannya, yang menjadi titik fokus mereka bukan pada bahasa, tetapi apa yang diamanatkan lewat peranti bahasa itu. Bahasa jurnalistik adalah yang digunakan oleh wartawan dinamakan bahasa pers atau bahasa jurnalistik. Bahasa jurnalistik memiliki sifat-sifat khas yaitu: singkat, padat, jelas, demokratis, sederhana, populis dan menarik. Bahasa jurnalistik didasarkan pada bahasa baku, tidak mengganggap sepi kaidah-kaidah tata bahasa, memperhatikan ejaan yang benar, dalam kosakata bahasa jurnalistik mengikuti perkembangan dalam masyarakat. Maka pada penelitian ini dirumuskan 2 (dua) rumusan masalah yaitu: Bagaimanakah penerapan bahasa jurnalistik dalam berita utama? Dan apakah bahasa jurnalistik sudah sesuai dalam berita utama? Tujuan penelitian ini untuk mengetahui penerapan dan kesesuaian bahasa jurnalistik pada berita utama di koran harian jurnal bogor edisi 07-13 Juni 2017 dan 05-11 Juli 2017. Penelitian ini menggunakan pendekatan kualitatif dengan metode wawancara mendalam (indepth interview) dimana periset melakukan wawancara langsung dengan Pimred koran harian jurnal bogor mengenai bagaimana penerapan bahasa jurnalistik pada berita utama berupa judul dan lead dan menganalisis isi dari kesesuaian bahasa jurnalistik pada berita utama berupa judul dan lead untuk mendeskripsikannya. Dengan menggunakan metode wawancara mendalam dapat menghasilkan data akurat langsung dari Pimred mengenai penerapan bahasa jurnalistik dengan menganalisis isi dari berita utama berupa judul dan lead bisa dilihat sudah cukup baik dengan kelengkapan prinsip-prinsip bahasa jurnalistik sudah terpenuhi namun ada beberapa judul yang masih kurang jelas dan kurang populis karena sebagian besar masyarakat masih awam dengan bahasa jurnalistik atau bahasa pers yang digunakan pada media cetak. Pada bagian lead sudah cukup jelas dengan apa yang akan disampaikan. Kesimpulannya penerapan dan kesesuaian bahasa jurnalistik pada berita utama sudah cukup baik karena konsisten terus memakai prinsip-prinsip bahasa jurnalistik akan tetapi dalam pelaksanaanya masih terdapat kesalahan pada judul yang kurang jelas.